Synthetic aperture radar observations with the Humboldt VHF ship-borne radar - Sarango, Martin F. (2001)
Motivated by the interest to study PMSE in Antarctica and Equatorial Electrojet along the southern Peruvian coasts, a VHF radar was developed and installed in 1998 by the Jicamarca Radar Observatory group on board the Peruvian research vessel BIC Humboldt (see description on a companion paper by Woodman, et. al). During the test runs of this radar, very strong echoes from the Andes were observed. In order to obtain profiles of the mountains and other facing targets, as glaciers in Antarctica, sorne efforts have been carried out to observe and process these echoes using Synthetic Aperture Radar (SAR) techniques SAR is a well known airborne (or spaceborne) radar mapping technique for generating high resolution maps of surface target areas and terrain. SAR applications include topographic mapping, surface deformation studies related to seismic activity and extraction of oíl and ground water, glaciology, and determination of Earth surface characteristics, including Jand surface, snow, oceans, sea ice and land ice. The Humboldt radar has been used to determine coastlines along the South American coasts for evaluation purposes. We also plan to use the same idea to perform observations using a radar on a truck. Ship-borne SAR cannot be used for surface mapping, because facing targets darken the targets behind them. However, this type of measurements become highly interesting when the coastline to be observed changes dynamically as in the case of glaciers and because of its low operational cost.